2018
DOI: 10.1177/2165079918769683
|View full text |Cite
|
Sign up to set email alerts
|

Work Hours, Overtime, and Break Time of Registered Nurses Working in Medium-Sized Korean Hospitals

Abstract: This cross-sectional study used quantitative survey data collected from registered nurses (RNs) who worked as staff nurses in medium-sized (300 beds or less) Korean hospitals. Data from 290 RNs were analyzed to examine the nature and prevalence of staff nurses' work hours, overtime, breaks, and related work conditions. The results showed that staff nurses working in medium-sized Korean hospitals worked 9.6 hours a day on average and had 1.5 breaks daily, including mealtime. The average number of days the nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 27 publications
1
31
0
2
Order By: Relevance
“…Therefore, researchers need to incorporate lifestyle‐related factors in future studies on nurse fatigue. Moreover, our participants were young ( M age = 26.77 ± 3.86) compared to 48.8 in the United States (Budde et al, ), but similar to other studies of Korean nurses (26.7, Bae et al, ; 27.5, Jung & Lee, ). The young age of nurses may reflect the propensity of Korean nurses leaving clinical settings at early stages in their career (Bae et al, ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, researchers need to incorporate lifestyle‐related factors in future studies on nurse fatigue. Moreover, our participants were young ( M age = 26.77 ± 3.86) compared to 48.8 in the United States (Budde et al, ), but similar to other studies of Korean nurses (26.7, Bae et al, ; 27.5, Jung & Lee, ). The young age of nurses may reflect the propensity of Korean nurses leaving clinical settings at early stages in their career (Bae et al, ).…”
Section: Discussionsupporting
confidence: 86%
“…The average break duration per 8‐hr shift, including mealtime breaks, is 30 min; about 65% of nurses miss mealtime breaks at least once a week (Lee et al, ). Bae, Hwang, and Lee () also reported that 45% of nurses working in medium‐sized (300 beds or less) Korean hospitals work typically more than 10 hr per day, often missing meals and not finding time to use the bathroom because of the heavy workload.…”
Section: Introductionmentioning
confidence: 99%
“…Job demands were explained with a high patient‐to‐nurse ratio, dissatisfaction with the job, unavailability of load‐lifting devices, the female gender, duration of LBP and load lifting. Similarly, previous research has emphasized most of these variables (Aiken et al, 2017; Bae et al, 2018; Barrientos‐Trigo et al, 2018; Dall’Ora et al, 2015; Yokota et al, 2019).…”
Section: Work Environment Conditionsmentioning
confidence: 83%
“…In inappropriate work environments, the percentage of nursing interventions required by patients which are not implemented is much greater compared to work environments with appropriate working conditions (Aiken et al, 2018; Cho et al, 2016). Inappropriate working conditions are the result of underdeveloped workplace infrastructure, poor work organisation, inadequate education and inappropriate staffing norms (Aiken et al, 2017, 2018; Bae, Hwang, & Lee, 2018; Barrientos‐Trigo et al, 2018; Cho et al, 2016). A shortage of nurses and working with limited resources jeopardize patient health and lower work autonomy (Aiken et al, 2017, 2018; Buchan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Stresorji zaposlenih v zdravstveni negi se močno razlikujejo glede na zahtevnost delovnega mesta (Henrich, et al, 2017). Pomemben dejavnik stresa zaposlenih v zdravstveni negi je izmensko delo (Zhang, et al, 2017;Kagamiyama & Yano, 2018), zato je izjemnega pomena zadosten čas počitka po končanem delavniku (Tsuchiya, et al, 2017;Bae, et al, 2018;Garcia, et al, 2018). Počitek je zaradi dela, ki presega delovni čas, lahko skrajšan.…”
Section: Uvodunclassified